HUMAN FACTORS STUDY OF QMC CLOTHING AND EQUIPMENT DURING COLD WEATHER TESTS OF THE PERSHING MISSILE SYSTEM - McGinnis, John M.; Zimmerer, Theodore (1962)
The primary purpose of the psychology laboratory participation in the test was to detect human factors problems associated with Quartermaster Corps standard clothing and equipment in the operation of the PERSHING Missile System and to report these problems to the responsible design and development groups. Secondary goals were to make preliminary studies concerning the new experimental integrated clothing system, and the feasibility of using electrically heated handwear for performing critical tasks during operation of the PERSHING equipment.